2018
DOI: 10.1111/jvim.15042
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferiInfection and Lyme Disease in North American Horses: A Consensus Statement

Abstract: Borrelia burgdorferi infection is common in horses living in Lyme endemic areas and the geographic range for exposure is increasing. Morbidity after B. burgdorferi infection in horses is unknown. Documented, naturally occurring syndromes attributed to B. burgdorferi infection in horses include neuroborreliosis, uveitis, and cutaneous pseudolymphoma. Although other clinical signs such as lameness and stiffness are reported in horses, these are often not well documented. Diagnosis of Lyme disease is based on exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 117 publications
1
94
1
7
Order By: Relevance
“…could expand this population. While viral exposure burdens are likely to be largely similar to burdens experienced by humans, horses in the northeastern U.S. are also frequently exposed to Borrelia burgdorferi (agent of Lyme disease) (69) and Sarcocystis neurona (agent of Equine protozoal myeloencephalitis) (70), and are continuously infested with or re-exposed to gastrointestinal nematodes (71). The horses in this study did not show signs of active infection or inflammation, as they all had normal complete blood count, serum amyloid A, iron indices, and globulins.…”
Section: Discussionmentioning
confidence: 99%
“…could expand this population. While viral exposure burdens are likely to be largely similar to burdens experienced by humans, horses in the northeastern U.S. are also frequently exposed to Borrelia burgdorferi (agent of Lyme disease) (69) and Sarcocystis neurona (agent of Equine protozoal myeloencephalitis) (70), and are continuously infested with or re-exposed to gastrointestinal nematodes (71). The horses in this study did not show signs of active infection or inflammation, as they all had normal complete blood count, serum amyloid A, iron indices, and globulins.…”
Section: Discussionmentioning
confidence: 99%
“…We provide the first report of a Bbsl-infected I. scapularis tick parasitizing a horse in Canada (Table 1). Although it was not possible to do a follow-up on this horse, Bbsl causes Lyme disease in horses [71]. The clinical symptoms of Lyme disease in horses include lameness, stiffness, neuroborreliosis, uveitis, and cutaneous pseudolymphoma [71].…”
Section: Ticks On Terrestrial Mammalsmentioning
confidence: 97%
“…Although it was not possible to do a follow-up on this horse, Bbsl causes Lyme disease in horses [71]. The clinical symptoms of Lyme disease in horses include lameness, stiffness, neuroborreliosis, uveitis, and cutaneous pseudolymphoma [71]. Congenital Lyme disease may occur in mares and foals, especially in Lyme disease endemic areas [72].…”
Section: Ticks On Terrestrial Mammalsmentioning
confidence: 99%
“…Several horses in our study had both CSF and serum tested for antibodies against B. burgdorferi . Our hospital uses the multiplex (a bead‐based multiple antigen ELISA assay) which detects antibody production to outer surface proteins (Osps) of B. burgdorferi . Without an ante‐mortem gold standard of diagnosis, this assay has been difficult to validate and a recent study found that paired serum and CSF multiplex results could not accurately diagnose neuroborreliosis in horses with a diagnosis confirmed on necropsy examination .…”
Section: Discussionmentioning
confidence: 99%
“…To be considered positive for EPM, a S. neurona serum : CSF antibody titer ratio of <100 was required . Patients were given a tentative antemortem diagnosis of neuroborreliosis if they had a serum : CSF ratio of <130 for antibodies to B. burgdorferi outer surface proteins, and all other likely diseases including EPM were excluded by appropriate diagnostic testing . Equids that were categorized as having idiopathic FNP were further grouped as “true idiopathic” or “not investigated”; “true idiopathic” was defined as cases that had no history or clinical signs of trauma, normal CSF analysis, normal UAE, and normal diagnostic imaging of the skull.…”
Section: Methodsmentioning
confidence: 99%